Ice-assisted electron-beam lithography for halide perovskite optoelectronic nanodevices. (November 2022) - Jin, Binbin; Hong, Yu; Li, Ziqing; Zhao, Ding; Lu, Yihan; Yao, Guangnan; Zheng, Rui; Bi, Gang; Zhang, Qing; Fang, Xiaosheng; Qiu, Min
Abstract: Metal halide perovskites (MHPs) have received substantial attention due to their impressive optoelectronic properties. In particular, nanoscale perovskite structures, such as nanowires (NWs) and nanoplates (NPs) are ideal building blocks for optoelectronic devices. However, metal electrodes can be hardly patterned on these materials with conventional lithographic methods due to the solvent sensitivity of perovskite crystals and alignment issues. Here, we report a solvent-free method to fabricate metal electrodes on perovskite NPs, which starts with the vapor deposition of water ice as an electron resist and ends in the sublimation of the ice followed by a "blow-off" process. The good compatibility between MHPs and ice as well as the in-situ imaging and patterning process guarantees the fabrication with high precision and resolution. Using this technique, we create metal electrodes on single-crystal MAPbBr3 NPs featuring a nanoscale gap of 296 nm and superior photodetection ability with responsivity of 653 A/W and detectivity of 3.08 × 10 13 Jones. Our study helps the widely-used electron-beam lithography break down barriers in processing perovskite materials, and provides an excellent platform to fully exploit their potentials in optoelectronic devices. Graphical Abstract: We report a solvent-free method to fabricate metal nanostructures on perovskites, which starts with the vapor deposition of water ice as an electron resist and ends in the sublimation of the ice followed by a "blow-off" process . ga1 Highlights: A perovskite-compatible lithography method was proposed to realize nanopatterning metal electrodes on single-crystalline perovskites. The in-situ imaging and patterning processes allow high-resolution nanofabrication with improved positioning accuracy. A perovskite photodetector with a small channel width of 296 nm has been obtained, which demonstrates superior photodetection ability with responsivity of 653 A/W and detectivity of 3.08 × 10 13 Jones.